Ensaios em opções reais e investimento sob incerteza - Gonçalves, Edson Daniel Lopes (2009)
The three essays in this thesis develop extensions and applications of Real Options Theory, related to very important policy issues in Brazil. The first one presents a pioneering analysis of bioprospecting, or the exploitation of biodiversity, driven by economic goals. Two alternative structures for the contractual arrangements between government and private sector, within the purpose of a sustainable economic use of the Brazilian biodiversity, are designed: (i) a R&D Project model, with uncertain maturity, in which the intensity of the Poisson process driving the maturity time is explicitly dependent on the biodiversity level at the granted location; (ii) a principal agent model, in which the State grants the exercise of an investment option to the biotech research firm. The second essay moves forward the analogy between put options and import quotas. The relevant parameters for pricing quota licenses are now endogenously obtained, via the interaction between an importing firm and domestic producers. Finally, the third paper makes an original analysis of the unofficial market for 'precatórios' a class of government bonds in Brazil, tied to specific federal, state or municipal debts. A model for pricing these securities, taking into account the current institutional environment affecting them at all three levels, is presented and calibrated.